Characterizing PALB2 intragenic duplication breakpoints in a triple-negative breast cancer case using long-read sequencing - Ban, Iulian O.; Chabert, Alice; Guignard, Thomas; Puechberty, Jacques; Cabello-Aguilar, Simon; Pujol, Pascal; Vendrell, Julie A.; Solassol, Jérôme (Frontiers in Oncology, 2024)
Introduction: Accurate identification and characterization of Large Genomic Rearrangements, especially duplications, are crucial for precise diagnosis and risk assessment. In this report, we characterized an intragenic duplication breakpoint of PALB2 LGR to determine its pathogenicity significance.Methods: A 52-year-old female with triple-negative breast cancer was diagnosed with a novel PALB2LGR. An efficient and accurate methodology was applied, combining long-read sequencing and transcript analysis for the rapid characterization of the LGR.Results: Duplication of exons 5 and 6 of PALB2 was validated by transcript analysis, inducing a frameshift. Long-read sequencing enabled the localization of breakpoints within Alu elements, providing insights into the mechanism of duplication via non-allelic homologous recombination.Using our combined methodology, we reclassified the PALB2 duplication as a pathogenic variant. This reclassification suggests a possible causative link between this specific genetic alteration and the aggressive phenotype of the patient.